Retrospective study of pathology-based investigative techniques for the assessment of diet-induced changes in liver and intestine of flatfish. Issue 2 (3rd April 2018) - Sirri, Rubina; Sarli, Giuseppe; Bianco, Carlo; Bonaldo, Alessio; Gatta, Pier Paolo; Fontanillas, Ramon; De Vico, Gionata; Carella, Francesca; Brachelente, Chiara; Parma, Luca; Mandrioli, Luciana
Abstract: This article proposes a systematic evaluation of methods pertaining to the pathology discipline (histology, histochemistry, ultrastructure, in situ techniques, image analysis including morphometry and fractal dimension analysis) employed to study liver and intestine status during a series of nutritional trials performed on flatfish species (common sole, Solea solea ; Senegal sole, Solea senegalensis and turbot, Scophthalmus maximus ) of commercial interest. Histology is the first step able to detect the normal architecture of the tissues or the possible occurring changes related to inflammation, degeneration and cell death. The evaluation of liver should include a scoring system to obtain semi-quantitative numerical data that are statistically analysable; histochemisty is a valid tool for identifying the type of cell content, together with ultrastructure that also permits the detection of even mild signs of cell damage. For the evaluation of the intestine, in situ techniques are useful together with fractal dimension analysis to determine the mucosal trophism, while ultrastructure can demonstrate cell injury. These considerations were resumed in a methodological flowchart as a valid tool to assess the fish health status when nutritional trials are planned.